Landing asymmetry in back tucked saltos and the effect of takeoff asymmetry - Hallgrimson, N. B.; Oates, A.; Erlandson, M.; Lanovaz, J. (ISBS Proceedings Archive (Michigan), 2020)
Landing asymmetry is an injury risk factor in gymnastics. This study examined whether takeoff force asymmetry is related to landing asymmetry during back tucked saltos in competitive gymnasts. Each gymnast performed an isometric leg strength test followed by multiple back tucked salto trials with no takeoff instruction, leaning with 60% asymmetry to the right, and 60% asymmetry to the left using a standard asymmetry index. Forces were measured at takeoff and landing. The novel experimental approach successfully produced distinct takeoff asymmetry levels. There was a significant rightward asymmetry in baseline landing peak vertical force, possibly due to right leg strength dominance. Landing asymmetry was also generated in the left and right leaning conditions. Both takeoff and leg strength asymmetries may play a role in landing force asymmetries in back tucked saltos.